FORMULATION AND EVALUATION OF ESOMEPRAZOLE FAST DISSOLVING BUCCAL FILMS - T, Balakrishna; S, Vidyadhara; Tegk, Murthy; A, Ramu; Rlc, Sasidhar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study deals with the formulation and evaluation of fast dissolving buccal films for effective treatment option in the gastroesophageal reflux disease. Methods: Esomeprazole fast dissolving buccal films are a convenient formulation of which can be taken with or without water. In the present investigation, polyvinyl alcohol and polyvinylpyrrolidone were used as film-forming agents and polyethylene glycol 400 is taken as plasticizer. Solvent evaporation method was used for the preparation of fast dissolving buccal films. Results: The films were prepared and evaluated for film thickness, folding endurance, dispersion test, drug content, and dissolution. The in vitro dissolution studies were carried out using simulated salivary fluid (pH 6.8 phosphate buffer). Conclusion: Among all the formulations, Formulation E7 was released up to 99.6% of the drug from the film within 5 min of time which exhibits faster absorption and also shows desirable characteristics of the film. The drug-excipient interaction studies WERE carried out by Fourier-transform infrared studies, differential scanning calorimetry analysis-X-diffraction studies, and scanning electron microscopic studies and the results revealed that there were no major interactions between the drugs and excipients used for the preparation of films.